Perlindungan Hukum bagi Pihak yang Dirugikan atas Penggunaan Jalan Umum sebagai Tempat Parkir Pribadi - Anak Agung Sagung Laksmi Dewi; Komang Wahyu Darmayanta; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2024)
People have the right to use public roads without interference from others who use public roads for private purposes. Vehicle owners usually use public roads as private parking lots. This study was conducted with the aim of describing how the responsibility of vehicle owners who use public roads as private parking lots and how the legal protection of parties who are harmed by the use of public roads as private parking lots. This study conducted research using a normative legal approach and legislative and conceptual studies. The findings of this study show that the level of liability of vehicle owners who use public spaces as a place to park private cars can vary depending on the legal regulations in force in a country. In Indonesia, there is a regulation number 22 of 2009 that regulates matters related to traffic and transportation on the road. Fines for parking violations are stipulated in Article 275 paragraph 1 of Law Number 22 Year 2009 on Road Traffic and Transportation (LLAJ Law). Parking on public roads is not permitted even if there are no no-parking signs posted. Roads are designed for the benefit of the general public and should not be used for the benefit of individuals.